Assessing habitat quality using the InVEST model in the Dire and Legedadi watersheds, central highland of Ethiopia: Implication for watershed management - Simeneh Admasu; Kumelachew Yeshitela; Mekuria Argaw (Sustainable Environment, 2023)
ABSTRACTThis study aimed to quantify and map habitat quality in the Dire and Legedadi watersheds between 1985 and 2022 using the InVEST habitat quality model. The purpose of this study was to assess the spatiotemporal changes in habitat quality in the Dire and Legedadi watersheds. The result showed, between 1985 and 2022, both watersheds experienced a significant decline in habitat quality. The extent of high habitat quality habitat in the Legadadi watershed has decreased significantly from 206 km2 in 1985 to 50.26 km2 in 2022. Similarly, high habitat quality habitat in the Dire watershed has gradually declined from 87.29 km2 in 1985 to 35.44 km2 in 2022. The construction of the Dire water reservoir in 1999 helped to maintain the extent of moderate habitat quality which increased from 6.93 km2 in 1995 to 25.36 km2 in 2010. The rapid expansion of farmland and settlement at the expense of natural vegetation was strongly linked to the decline in habitat quality. As a result, appropriate watershed management intervention is required. Therefore, the outcome of this research will provide a scientific basis for future ecosystem monitoring to monitor the impacts of watershed management interventions.